The importance of results of determining the reticulocytes parameters in clinical practice - Сергиенко, Л. И. (REPRODUCTIVE ENDOCRINOLOGY, 2015)
The article presents data on the morphology and physiology of reticulocytes and described methods for determining the parameters of quantity and quality, in particular by means of hematology analyzers. Clinical significance of reticulocytes parameters described. Study parameters of reticulocytes in clinical practice are necessary to evaluate the activity of erythropoiesis at conditions involving blood loss or hemolysis; to identify disorders of regenerative capacity of the bone marrow in deficiency of iron, vitamin B12, В6, folate, copper, and monitoring of appropriate therapy; to assess the state of erythropoiesis during treatment with erythropoietin, etc.